Efficacy of Glufosinate Ammonium Herbicide on Weed Control, Impact on Soil Chemical Properties and Heavy Metal Accumulation in Cocoa Plantations. - Aremu-Dele, Olufemi; Ugioro, Osas; Ayegboyin, Kayode Olufemi; Nduka, Beatrice Abanum; Adeosun, Seun; Ibe, Osita; Asowata, Frank; Oyeledun, K.O.; Oyediran, Uthman; Salisu, Umar; Agboluaje, Adura; Shuaib, Taye (Indonesian Coffee and Cocoa Research Institute, 2024)
Prolonged use of commonly used herbicides by cocoa farmers such as paraquat and glyphosate have been observed to have residual effects on the environment. Therefore there is a need to screen herbicides such as Glufosinate ammonium-based herbicides for use by cocoa farmers. The experiment was set up at the cocoa experimental plot of the Cocoa Research Institute of Nigeria Headquarters in Ibadan. The 3 treatments which were arranged in a Randomized Complete Block Design are slashing, 100 mls and 200 mls of Glufosinate ammonium per 16L of water (100 mls/16L and 200 mls/16L). Each experimental unit was 6 m Ã— 6 m comprising nine cocoa stands. The treatments were replicated 3 times. Data on the soil's initial physico-chemical properties and after 3 months of each treatment were recorded. Mineral and heavy metal analysis of the leaves and pods before spraying and 3 months after spraying were recorded. The % weed control of the treatments was also observed. Treatment means were separated using the Least Significant Difference (LSD) at a 0.05% probability level. Results showed that Glufosinate ammonium applied at both rates did not load the soil, cocoa leaves and cocoa beans with heavy metals. 200 mls/16L had 85.00% weed control followed by 100 mls/16L (62.70%) and slashing (51.00%) which both had the same statistical result. Glufosinate ammonium at 100 mls/16L can replace slashing to eliminate drudgery while Glufosinate ammonium at 200 mls/16L can be used for more effective weed control without negative effects on the environment and the crop.